2017
DOI: 10.1039/c7dt00340d
|View full text |Cite
|
Sign up to set email alerts
|

Structural origin of the enhanced ionic conductivity upon Nb doping in Sr11Mo4O23 defective double perovskite

Abstract: We report a substantial enhancement of the oxide-ion conductivity in SrMoO achieved by Nb doping the Mo sites. This series responds to the formula: SrMoNbO (with x = 0.0, 0.5 and 1.0). The original structure can be related to the conventional double perovskite; however, it presents a broken corner sharing connectivity of the octahedral framework, hence leading to a complex and highly defective network. The samples were prepared via citrate precursor method, followed by thermal treatments at 1300 °C for 12 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This is in contrast with recent reports that have described the structure of Sr 22 Three later reports also looked at the high temperature behavior of this phase, Nb doped samples, and Ti doped samples. [23][24][25] The undoped Sr 11 Mo 4 O 23 was reported as tetragonal at all temperatures, while the doped samples were reported to be tetragonal at room temperature but transition to the cubic structure at higher temperature. We achieved a satisfactory Rietveld refinement (R p 5.72, R wp 8.66, R F 2 14.3) using our synchrotron X-ray data with the cubic space group 3 � and a lattice parameter of a = 16.4108 Å.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with recent reports that have described the structure of Sr 22 Three later reports also looked at the high temperature behavior of this phase, Nb doped samples, and Ti doped samples. [23][24][25] The undoped Sr 11 Mo 4 O 23 was reported as tetragonal at all temperatures, while the doped samples were reported to be tetragonal at room temperature but transition to the cubic structure at higher temperature. We achieved a satisfactory Rietveld refinement (R p 5.72, R wp 8.66, R F 2 14.3) using our synchrotron X-ray data with the cubic space group 3 � and a lattice parameter of a = 16.4108 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Four recent studies have looked at the crystal structure of Sr 11 Mo 4 O 23 and its ionic conductivity. [22][23][24][25] The conductivity is moderate for the undoped material, but can be increased to values as high as 2.7×10 -2 S . cm -1 and 1.8×10 -2 S .…”
Section: Introductionmentioning
confidence: 99%
“…5 for both air and helium runs. This reversible process has been explained by proposing the removal and uptake of O 2 , H 2 O or CO 2 ; 14,17,19,21 however, these works contain no conclusive evidences to conrm or discard any of them. The thermal evolution of fragment signals from mass spectroscopy is shown in Fig.…”
Section: Thermogravimetric Analysis-mass Spectrometry (Tga-ms)mentioning
confidence: 99%
“…In fact, some enhancement in the conductivity has been obtained upon Nb, Ti and Al doping. [17][18][19] On the other hand, King et al presented novel structural evidences and reported Sr 11 Mo 4 O 23 as cubic (Fd 3m), the difference between both materials only residing in the annealing temperature. 20 In addition, in a recent work, Kharton et al studied the ionic conductivity and also observed the mass changes with temperature.…”
Section: Introductionmentioning
confidence: 99%